PEMANFAATAN MINYAK SEREH WANGI (Cymbopogon nardus) SEBAGAI VAPORIZING MAT (MV) ELEKTRIK UNTUK PEMBERANTASAN LALAT RUMAH (Musca domestica) - Yamtana; Saputra, Rizki; Eko Windarso, Sarjito (Poltekkes Kemenkes Bengkulu, 2022)
The house fly is one of the mechanical vectors of transmission or spread of disease whose control has been continuously studied. One of the most commonly used ways to eradicate flies is to use insecticides. One way is to use citronella leaves (Cymbopogon nardus). The active ingredients of citronella leaves (Cymbopogon nardus) are citronellal and geraniol. This study aims to determine the effectiveness of citronella citronella oil (Cymbopogon nardus) using the vaporizing mat method as an insecticide against the house fly (Musca domestica) in tackling the growth and development of the house fly (Musca domestica). This research is an experimental research workshop on environmental health at the Poltekkes Kemenkes Yogyakarta using the pre-test only control group design method. The samples used in this study were a number of house flies (Musca domestica) which had met the inclusion criteria and had been selected and obtained from the results of being caught around TPS Ngundi Raharjo using paper cups. Citronella citronella (Cymbogon nardus) oil is heated through an electric mat into a 25cm x 25cm x 25cm net cage filled with 10 adult house flies (Musca domestica). Repetition was carried out 5 times at time intervals, namely the 1st, 2nd, 3rd, 4th, 5th, 6th and 24th hours. The treatment used was the concentration of citronella oil (Cymbopogon nardus) of 15%, 20% and 25% and control (aqueous solution). At the 1st, 2nd, 3rd, 4th, 5th, 6th and 24th hours each observation shows a significance value (sig. <0.05) and it is concluded that there is a difference which is very significant between variations in the concentration of citronella oil (Cymbopogon nardus) as an insecticide against house flies (Musca domestica). Insecticide potency is not only influenced by the size of the concentration, but also by the length of time of observation. Keywords: Insecticides, flies, citronella oil, vaporizing mat